Efficient recovery and regeneration of waste graphite through microwave stripping from spent batteries anode for high-performance lithium-ion batteries. (20th January 2022) - Yuwen, Chao; Liu, Bingguo; Zhang, Hui; Tian, Shihong; Zhang, Libo; Guo, Shenghui; Zhou, Baocheng
Abstract: Green and efficient separation of waste graphite (WG) from the copper foil of spent lithium-ion batteries (LIBs) anode can significantly reduce the pollution caused by the LIBs anode and relieve the pressure of graphite demand. Here, a clever technique for the excellent microwave absorption ability of LIBs anode makes the binder and electrolyte in WG volatilize quickly in the microwave field, resulting in an efficient separation of WG from the copper foil. In addition, microwave radiation also causes the remaining lithium in WG to form Li2 CO3, which can be extracted by water leaching under CO2 and then heating, lithium-containing wastewater can also be recycled for the leaching of lithium. The purity of reconstituted graphite (RG) is improved after water leaching and heating, and the content of fluorine impurity is reduced from 15.87% to 0.28%. RG also retains the orderly layered structure and restores the electrochemical activity, the initial discharge specific capacity and coulombic efficiency at 0.1 C are 435.2 mAh·g −1 and 80.6%, respectively. Moreover, it reveals the superior cycling stability and rate performance comparable with commercial graphite. The proposed method provides an industrialized, low-energy-consumption pathway for the clean recovery and re-use of spent LIBs anode, which provides a reference basis for the disposal of other hazardous carbon-containing solid wastes. Graphical abstract: Image 1 Highlights: Declared feasibility of microwave stripping waste graphite from copper foil in LIBs anode. The microwave absorption capacity of the anode current collector of LIBs was firstly tested. Li in waste graphite was enriched in the form of Li2 CO3 . The regenerated graphite had high capacity and good cycling performance.